The Role of the Gut Microbiota in the Development of Ischemic Stroke - Wang, Jinchen; Zhang, Hongfei; He, Jianying; Xiong, Xiaoxing (Frontiers in Immunology, 2022)
An increasing number of studies have focused on the gut microbiota and its relationship with various neurological diseases. The gut microbiota can affect the metabolic status of the body, in addition to having an important impact on blood pressure, blood glucose, and atherosclerosis, all of which are risk factors for ischemic stroke. In this review, we summarized studies that included the physiological function of the gut microbiota and gut microbiota disorders related to the central nervous system, thus providing novel ideas for the prevention and treatment of ischemic stroke.